Can We Measure Memes? - McNamara, Adam (Frontiers in Evolutionary Neuroscience, 2011)
Memes are the fundamental unit of cultural evolution and have been left upon the periphery of cognitive neuroscience due to their inexact definition and the consequent presumption that they are impossible to measure. Here it is argued that although a precise definition of memes is rather difficult it does not preclude highly controlled experiments studying the neural substrates of their initiation and replication. In this paper, memes are termed as either internally or externally represented (i-memes / e-memes) in relation to whether they are represented as a neural substrate within the Central Nervous System (CNS) or in some other form within our environment. It is argued that neuroimaging technology is now sufficiently advanced to image the connectivity profiles of i-memes and critically, to measure changes to i-memes over time, i.e., as they evolve. It is argued that it is wrong to simply pass off memes as an alternative term for ‘stimulus’ and ‘learnt associations’ as it does not accurately account for the way in which natural stimuli may dynamically ‘evolve’ as clearly observed in our cultural lives.